The effect of firm size, financial ratios and cash flow on stock return - Atika Yuliarti; Lucia Ari Diyani (Universitas Hayam Wuruk Perbanas, 2018)
Stocks are kinds of financial instruments with high returns that have high levels of uncertainty. Before decide to invest the investor needs to formulate the expected rate of return. Companies with good financial performance will increase the value of the company so that the company's stock price increases and stock return also increases. The purpose of this research was to determine the effect of Firm Size, Return On Equity, Market Book Ratio, Current Ratio, Cash Flow from Operating Activities, Cash Flow from Investing Activities and Cash Flow from Financing Activities to Stock Return. The object of research used were seven pharmaceutical industry companies listed in BEI period the 2011-2016 with multiple analysis methods. The results of this study indicate that partially Market Book Ratio has a significant positive effect on Stock Return and Cash Flow from Financing Activities has a significant negative effect on Stock Return while Firm Size, Return On Equity, Current Ratio Cash Flow from Operating and Â Investing Activities have no significant effect on Stock Return. All variables in this study simultaneously have a significant effect on Stock Return.